Interventions: race, culture, and population via the thought of A.P. Elkin. (1st October 2016) - Griffiths, Michael R.
ABSTRACT: In key texts of Australian history, indigenous culture was seen as a device for delineating the boundaries of populations in such a way as to see it depicted as no longer focusing on race or physical difference. Focusing on several key moments in twentieth-century Australian indigenous policy when interventions in indigenous populations were first justified through a move from race to culture, this essay argues first that intervention into culture often retains essentialist assumptions about difference that recapitulate thought previously associated with race and physical difference. The article examines the thought of A.P. Elkin to ask whether the move from racial absorption to cultural assimilation can be characterised as an epistemic break in the Foucaultian sense or whether it contains instances of continuity in mechanisms of power. What happens, the article asks when populations come to be identified as spheres of cultural difference to be governed and intervened into using the techniques of the physical previously associated with race? The answer to this question has implicit consequences not only for the period examined but implicitly for more recent debates in intervention into indigenous lives.